Vertical-SI-nanowire based nonvolatile flash memory for 3-D ultrahigh density application - Sun, Yuan (2012)
Nonvolatile memory (NVM) technology is going through a fast evolution amongst the semiconductor technologies in the last decade. To satisfy the increasing demand of flash memory, the memory density has been continuously increased through aggressive scaling of the device dimensions in 2-dimensional (2-D) plane. However, the cell size shrinking in 2-D is getting more and more difficult beyond sub-20-nm technology node due to concerns on lithography, coupling ratio, and crosstalk interference.